(untitled) (American Journal of Business Management, Economics and Banking, 2024)
Artificial Intelligence (AI) has emerged as a transformative force in addressing global challenges, particularly in achieving the United Nations Sustainable Development Goals (SDGs). By automating processes, enhancing efficiency, and enabling data-driven decision-making, AI is redefining how societies manage environmental, economic, and social systems. This article explores the multifaceted role of AI in driving sustainable development, including its applications in climate change mitigation, resource optimization, health care, and education. It also examines the challenges associated with integrating AI into sustainability strategies, such as ethical concerns, data privacy, and the digital divide. The study underscores the need for collaborative efforts among governments, industries, and researchers to harness AI responsibly for a sustainable future.